Phenotypic variability among patients with hyperornithinaemia–hyperammonaemia–homocitrullinuria syndrome homozygous for the delF188 mutation in SLC25A15. Issue 11 (31st October 2008) - Debray, F-G; Lambert, M; Lemieux, B; Soucy, J F; Drouin, R; Fenyves, D; Dubé, J; Maranda, B; Laframboise, R; Mitchell, G A
Abstract : Background: Hyperornithinaemia–hyperammonaemia–homocitrullinuria (HHH) syndrome (OMIM 238970) is caused by impaired ornithine transport across the inner mitochondrial membrane due to mutations in SLC25A15 . To date, 22 different mutations of the SLC25A15 gene have been described in 49 patients belonging to 31 unrelated families. Objective: To further delineate the phenotypic spectrum of HHH syndrome from a description of a genetically homogeneous cohort of patients and identify prognostic factors based on long-term follow-up. Methods: Sixteen French-Canadian patients were retrospectively and prospectively clinically assessed. Results: Owing to a founder effect, 15 of the 16 patients were homozygous for the F188del mutation in the SLC25A15 gene. The main clinical features at presentation were liver dysfunction (6/16) and neurological disease (9/16), including chronic neurological symptoms (6/9) and acute encephalopathy (3/9). Hyperammonaemia was not constant and usually mild and uncommon after start of treatment. Long-term follow-up showed that variable intellectual impairment and lower limb spasticity often occur, together or separately, with no obvious relationship to age at diagnosis and compliance with treatment. Conclusion: We report the largest known cohort to date of patients with HHH syndrome. A similar range of severity occurred in the clinical course and outcome of patients homozygous for delF188 and in the 33 other reported patients compiled from the literature. The poor clinical outcome of some patients with HHH syndrome despite early treatment and repeatedly normal plasma ammonia levels emphasises the need to better understand the pathophysiology and to reconsider the therapeutic goals for HHH.